Hak Politik Perempuan dalam Sistem Pemilihan Umum di Indonesia - Sarah Tri Faustine Sagala; Mirza Nasution; Yusrin Yusrin (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the legal construction of women’s political rights within Indonesia’s electoral system through a normative-doctrinal approach grounded in statutory interpretation, legal principles, and doctrinal analysis. The research focuses on the coherence between constitutional guarantees, particularly under the 1945 Constitution, and the regulatory framework governing elections, including Law Number 7 of 2017 and Law Number 7 of 1984 as a ratification instrument of CEDAW. By employing grammatical, systematic, and teleological interpretation, the study identifies normative tensions between formal equality and substantive representation in the implementation of affirmative action policies. The findings reveal that despite the existence of a 30 percent quota requirement in candidate nomination, structural and regulatory inconsistencies continue to limit the effective realization of women’s political participation. Comparative insights drawn from international data further demonstrate that Indonesia’s position reflects partial compliance with global standards of gender representation. This study contributes to legal scholarship by proposing a reconstruction of electoral norms that strengthens enforceability, harmonizes regulatory provisions, and advances substantive gender equality within democratic governance.